Electoral Manipulation via Media: Theory and Evidence - Wojtasik, Waldemar (Communication Today, 2025)
The mediatization of political communication makes it possible to increase the number of electoral manipulations via media, whose aim is to change the competitive positions of subjects running in the election. Manipulation activities give the opportunity to affect voters’ decisions in a way that would be impossible without the media. Manipulations are performed by politicians, political parties or other subjects acting on their behalf. They can also be initiated by the governments of countries interested in influencing the directions of political changes in other countries. The presented study shows the possible use of media potential to manipulate election results. Such manipulations are possible in the situation of instrumental influence on the functioning of free and pluralistic media that allow political communication, or in the situation of instrumental influence on information, involving the creation and transmission of information in a non-objective way. The text focuses on the following types of electoral manipulations: (1) political influence of the government on the media; (2) political ‘agencification’ of the media; (3) limitations on carrying out election campaigns in the media; (4) the use of big data in political communication.